Evaluating Employee Performance: The Influence of Occupational Safety and Health, Motivation, Work Environment - Rofikul Amin; Putra Sari'ul Ichsan (Innovation Business Management and Accounting Journal, 2024)
This research was conducted at PT Pelindo III (Persero) Sub Regional Java Surabaya with a focus on analyzing the impact of Occupational Safety and Health (K3), work motivation, and work environment on employee performance in facing the challenges of globalization. By involving 50 employees from PT Pelindo III (Persero) Sub Regional Java Surabaya as samples, the analysis was carried out using the multiple linear regression method. The findings show that K3 has a significant effect on employee performance, where employees who work in safe and healthy conditions tend to be more productive and perform well, reducing the risk of injury or work accidents. However, work motivation and work environment do not show a significant influence on employee performance. This research provides an in-depth understanding of the factors that influence employee performance in certain work environments in the context of globalization. The implications can be used by company management to improve K3 conditions, which will improve employee performance and overall operational efficiency. In addition, this research highlights the importance of adapting to the challenges of globalization through better management of occupational safety and health. Thus, this research is not only useful for PT Pelindo III (Persero) Sub Regional Java Surabaya, but can also be a reference for other companies in efforts to improve employee welfare in the era of globalization.